O'Reilly Velocity Conference 2019, San Jose, California. (O'Reilly Media, 2019)
"O'Reilly Media's Velocity San Jose 2019 conference had one overarching goal: offer conference attendees the opportunity to gather expert insight on building and maintaining cloud native systems. How did Velocity meet that goal? By giving the world's best cloud native system engineers, SREs, and DevOps experts the chance to share their experiences. For example: Alex Chen (Alibaba Cloud) described how cloud native storage products such as table storage, object storage, and log storage enabled the Alibaba platform to handle RMB 10B worth of sales in two minutes and five seconds. Ory Segal's (PureSec) revealed how attackers approach and exploit the weaknesses of serverless and what you can do about it. Nivia Henry (Spotify) demonstrated how an algorithm is built and what you can do to catch, reduce, or eliminate the algorithmic biases that produce infamous events like Tay the racist Twitter Bot. This video compilation contains all of these talks plus the best keynotes, tutorials, and tech sessions delivered at Velocity San Jose 2019"--Resource description page